Specific features of production of Istobensky variety shallot grown by transplanting method - V. M. Motov; A. V. Denisova; O. A. Cheglakova; M. V. Motova (Аграрная наука Евро-Северо-Востока, 2020)
Currently, shallot (Allium ascalonicum L.) is a popular crop, it requires study and development of new varieties. Above all, it needs industrial production technology. The article presents the results of 2015-2019 research on the cultivation of salad shallot by transplanting method in the conditions of the Kirov region (North-East of the European part of Russia). It has been established that growing the Istobensky variety through seedlings allows to get a full-fledged marketable bulb during the growing season. To obtain full-fledged seedlings the seeds are to be sown on the first days of April. The optimal age of seedlings from germination to planting into open ground is 40 days. Depending on the variant, from 1 to 5 pieces of plants were grown in each cell. The control variant had one plant. During artificial illumination, LED lamps with light intensity of 5000-7000 lm were used. The recommended growing period was 20-25 days; the illumination period - 14 hours. Seedlings were grown in a polycarbonate greenhouse during 18-20 days, followed by planting into the open ground. The maximum yield with minimum cost of seeds was obtained by growing three plants in one cell. When grown by the transplanting method, the maximum bulb size of 400 g was obtained in 2016. The studies proved that the maximum yield of 5.8 kg/m2 (+1.6 to the control at LSD05 = 0.7) was obtained when sowing seeds on April, 4. Planting two plants into a hole reduced the average bulb weight by 33%, three – 40; four – 57; and five – 68% compared with the control. The study have shown that shallot of the Istobensky variety is suitable for the transplanting method of growing bulbs from seeds. During one growing period it is possible to get full-fledged bulbs of salad use with an average weight of 100-131 g, with a dry matter content of 2.99%, ascorbic acid – 13.99%, acidity – 0.61%.